Encontros de formação na educação infantil : experiências partilhadas no estágio supervisionado do curso de pedagogia - Silva, Priscila Alves (2016)
Investigate the formative processes that are built in the meetings between Pedagogy course student teacher, professore and assist the CEI Criarte, by sharing knowledge in the mediation Teachinng Practicum in kindergarten presents as guiding this research. We seek to understand specifically how the teacher and the Auxiliary of Child Education at the meeting with the degree course in Student Teachers who perform the discipline Teachinng Practicum in Child Education, share their experiences and through them form. We have analyzed the formative processes that were built by means of sharing of teachers and student teachers experience in the meetings of the Practicum in order to signal the Teachinng Practicum in Child Education, as the privileged place the initial formation of continuing education teacher and assistant of Education school children's training field. We develop research in the formative spaces managed by the Education Center, Federal University of Espírito Santo, and the degree course in Pedagogy and Child Center Criarte. The narrative research was used as the conductor axis of the study, in dialogue with the reflexive interview and participant observation. We also analyzed the academic production in the electronic databases Scielo and CAPES, on the subject of Teachinng Practicum in teacher formation and student teachers from Chlil Education. Supported in teacher training ideas, Nóvoa (2002; 2009); experience, Benjamin (2012); Larrosa (2015); Souza (2006; 2007); and Supervised, pepper; Lima (2012); Ventorim (2009; 2011), we base the assumptions of this study. The results point to the strengthening of Teachinng Practicum and the school as a meeting between subjects in training that by sharing their experiences build their professional action repertoires, reflect on their practices and training processes, what it is to be teacher Children's. However, also point, disagreements signals that weakened the participation of students teacher in the realization Practicum, which implies the need for the CEI Criarte consolidate as Teachinng Practicum field, that is, as the locus of articulation between initial and continuing education of teachers Child Education.